The Influence of Madrasah Head Leadership and Work Climate on Teacher Performance of Madrasah Aliyah Negeri 2 Bandung District - Fiyul, Arfiani Yulianti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Research with the aim of analyzing the influence of leadership from Madrasah heads and to analyze work climate on teacher performance. Data collection techniques are (1). Documentation in the form of archives regarding the number of teachers, Madrasah profiles, and Madrasah facilities. (2). The questionnaire includes written questions to obtain information from respondents (3). Interview with respondents to obtain complete information. (4). Observation to obtain observed data from the research environment. The research results were obtained from simple linear regression calculations and multiple regression. From the results of a simple linear regression, it can be concluded that there is a significant influence of Madrasah head leadership on teacher performance, namely 0.26%), and there is an influence between work climate on teacher performance, namely 0.031%). The influence of Madrasah head leadership and work climate on teacher performance is -0.0010%).